Memory and trauma of the Portuguese agrarian reform: A case study - Almeida, M. (2007)
The author analyses the Agrarian Reform in the southern part of Portugal, which took place as a result of radical legislation issued right after the Revolution of April 25th, 1974. The municipality of Avis is presented as an example of this movement, because of its charismatic leaders and the huge adhesion of their followers, who set in motion land occupations throughout the entire region. Personal and group motivations are described, using both written (institutional and literary) and oral sources. Thirty years later, consequences of the movement can still be found in the region and new ways of life were established in order to cope with the changing rural world.